2019
DOI: 10.2196/14753
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mobile Apps Targeted at Patients With Spondyloarthritis for Disease Monitoring: Systematic App Search

Abstract: Background There are many apps developed for patients with spondyloarthritis in the market, but their purpose and quality are not objectively evaluated. Objective The objective of this study was to identify and evaluate existing publicly available, high-quality apps that use validated measurement instruments for monitoring spondyloarthritis disease activity. Methods We conducted a review of apps available on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
(34 reference statements)
3
18
0
Order By: Relevance
“…Many symptom-tracking apps for rheumatic disease did not use validated instruments [ 16 , 29 ]; only 2 apps in this study used validated instruments to track patients’ symptoms. iRheuma used the ASDAS, BASDAI, and BASFI to track users’ disease activity and functional ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many symptom-tracking apps for rheumatic disease did not use validated instruments [ 16 , 29 ]; only 2 apps in this study used validated instruments to track patients’ symptoms. iRheuma used the ASDAS, BASDAI, and BASFI to track users’ disease activity and functional ability.…”
Section: Discussionmentioning
confidence: 99%
“…Both apps lacked the ability to directly transmit data to health care providers. Although evidence has suggested that mobile apps that use a validated instrument and have a tracking function may be useful for patients with arthritis for symptom monitoring [ 16 , 29 ], most of these apps, as well as the ones from our study, were not assessed in clinical trials. Thus, future studies should explore the effects of these apps on health and economic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphone technology, including apps [ 19 ] and app integrated wearable sensors [ 20 ], offers further chronic disease management potential. Moreover, the technological capacity, popularity, availability, and increased smartphone ownership globally, including in developing nations, promotes the smartphone as an attractive tool to assist patient self-management, continuous symptoms and vital sign monitoring, and communication between patients and physicians [ 21 , 22 ]. Furthermore, chronic disease management apps are beneficial in improving patients’ clinical outcomes and assisting in providing necessary medical care [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the technological capacity, popularity, availability, and increased smartphone ownership globally, including in developing nations, promotes the smartphone as an attractive tool to assist patient self-management, continuous symptoms and vital sign monitoring, and communication between patients and physicians [ 21 , 22 ]. Furthermore, chronic disease management apps are beneficial in improving patients’ clinical outcomes and assisting in providing necessary medical care [ 22 ]. Additionally, apps integrated with built-in smartphone sensors and wearable external sensors can capture numerous health parameters to deliver personalised healthcare solutions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%